Desaturation, dioxygenation, and monooxygenation reactions catalyzed by naphthalene dioxygenase from Pseudomonas sp. strain 9816-4. - Gibson, D T (1995)
The stereospecific oxidation of indan and indene was examined with mutant and recombinant strains expressing naphthalene dioxygenase of Pseudomonas sp. strain 9816-4. Pseudomonas sp. strain 9816/11 and Escherichia coli JM109(DE3)[pDTG141] oxidized indan to (+)-(1S)-indanol, (+)-cis-(1R,2S)-indandiol, (+)-(1S)-indenol, and 1-indanone. The same strains oxidized indene to (+)-cis-(1R,2S)-indandiol and (+)-(1S)-indenol. Purified naphthalene dioxygenase oxidized indan to the same four products formed by strains 9816/11 and JM109(DE3)[pDTG141]. In addition, indene was identified as an intermediate in indan oxidation. The major products formed from indene by purified naphthalene dioxygenase were (+)-(1S)-indenol and (+)-(1R,2S)-indandiol. The results show that naphthalene dioxygenase catalyzes the enantiospecific monooxygenation of indan to (+)-(1S)-indanol and the desaturation of indan to indene, which then serves as a substrate for the formation of (+)-(1R,2S)-indandiol and (+)-(1S)-indenol. The relationship of the desaturase, monooxygenase, and dioxygenase activities of naphthalene dioxygenase is discussed with reference to reactions catalyzed by toluene dioxygenase, plant desaturases, cytochrome P-450, methane monooxygenase, and other bacterial monooxygenases.